Altered hemispheric asymmetry of attentional networks in patients with pituitary adenoma: an event-related potential study - Wang, Shuochen; Fu, Zhenghao; Sun, Yuanyi; Zhang, Meng; Chen, Aobo; Cao, Chenglong; Song, Jian (Frontiers in Neuroscience, 2023)
Background Emerging evidence has been reported of attentional dysfunction in pituitary adenoma patients. However, the effect of pituitary adenomas on lateralized attention network efficiency remained to be clear. Thus, the present study aimed to investigate the impairment of lateralized attention networks in patients with pituitary adenoma. Methods Eighteen pituitary adenoma patients (PA group) and 20 healthy controls (HCs) were included in this study. Both behavioral results and event-related potentials (ERPs) were acquired while subjects performed the Lateralized Attention Network Test (LANT). Results Behavioral performances indicated the PA group had a slower reaction time and a similar error rate relative to the HCs group. Meanwhile, significantly increased executive control network efficiency suggested the dysfunction of inhibition control in PA patients. Regarding ERP results, there were no group differences in the alerting and orienting networks. The target-related P3 was significantly reduced in the PA group, suggesting an impairment of executive control function and attentional resources allocation. Moreover, the mean amplitude of P3 was significantly lateralized to the right hemisphere, and interacted with the visual field, exhibiting that the right hemisphere dominated the bilateral visual field, whereas the left hemisphere dominated the left visual field. In the specific high-conflict condition, the pattern of hemispheric asymmetry in the PA group was altered due to a mixed effect resulting from the compensatory recruitment of attentional resources in the left central parietal area and the destructive effects of hyperprolactinemia. Conclusion These findings suggested that, in the lateralized condition, the decreased P3 in the right central parietal area and the diminished hemispheric asymmetry under high conflict load, may serve as the potential biomarkers of attentional dysfunction in patients with pituitary adenoma.